0162 Sleep in Pacific Ocean Populations: A Scoping Review. (25th May 2022) - Gilles, Allyson; Frakes, Elizabeth; Aitaoto, Nia; Hazelbaker, Avery; Nonu, Sitiveni; Tran, Julianna; Baron, Kelly
Abstract: Introduction: Sleep research focused on individuals categorized as Native Hawaiian/Pacific Islander suggests that sleep deficiencies(short sleep, insomnia symptoms) are highly prevalent among adults. Given the large degree of diversity related to family origin of Pacific ocean populations and assimilation, a more robust understanding of unique risk factors related to sleep challenges for these heterogenous communities is warranted. We are conducting a scoping review of studies that examine associations of health, practice, sociodemographic, and influential mechanisms with sleep in Pacific ocean populations. Methods: A literature search conducted in Medline, Embase, Psychinfo, and Cochrane encompassed three domains: sleep-related and sleep-disorder terms, oceanic island and ancestry names, and sub-population names inclusive of the geographic regions of Polynesia, Micronesia, and Melanesia. The primary search retrieved 2364 articles. Studies were selected by abstract and full text analysis by one reviewer, followed by independent data extraction by four reviewers. Using a standardized form, synthesis of results and assessment of sample demographics, sampling strategy, sleep data source and findings, theoretical framework, and covariates was conducted per article. Inclusion criteria included articles with at least one quantitative sleep-related finding for a Pacific island population. We excluded non-primary research articles. Studies that categorically combined other racial/ethnic groups with Pacific ocean populations(Asian/Pacific Islander) or geographic regions(Asian-Pacific region) in reporting findings were excluded. Results: Of the 99 articles included in the review, 18 included children/adolescents, 56 included adults, 13 included multiple age groups, and 12 reported no or only mean participant age. Seventy-two studies allowed participants to self-identify their major ethnic group as a single race(e.g., Tongan, Kirbati). Seventeen studies included objective methods(e.g., actigraphy). The most common sleep-related factors were issues of sleep patterns(n=51), physical health(n=43), mental health(n=28), socioeconomic deprivation(n=26), daytime sleepiness/fatigue(n=20), sleep disorders or symptoms (snoring)(n=17), sleep-supporting practices(n=9), and integration into main culture/born in US(n=3). Conclusion: Preliminary results suggest that few studies have examined identifiable factors that may impact sleep within diverse Pacific ocean communities, with most studies focused on adults, self-reporting, and sleep pattern problems. Future studies should examine underlying mechanisms related to sleep deficiencies in both children and adults to better understand variability in risk across the lifespan. Support (If Any):